Querelles et légitimations - Alain Viala (Carnets)
History of the the French literary canon can be analyzed from two particular dispites. The first one at the origin of this canon was held in 1738 between erudites who were trying to elaborate and publish a list of canonical French writers. The other one, the most recent at date, was happened en 2000 about national programmes for High Schools. 1738 showed that the main concern was not to decide who are the authors to be legitimated but the ways of use of Literature. Similarly, on 2000, the matter was the question of the reasons to teach legitimated works, from professional and politics points of view. Therefore, what happens here is that the criteria to define what is legitimated are social rather than purely esthetical.